European and US constitutionalism - Nolte, Georg, 1959- (Cambridge University Press, 2005)
This book asks whether and how far constitutional theory and judicial practice differ between Europe and the United States. The areas explored are freedom of speech, human dignity, duty of the state to protect individuals from harm, adjudication by constitutional and other courts, and democratic theory and international influences.